1994
DOI: 10.2307/3869826
|View full text |Cite|
|
Sign up to set email alerts
|

An Arabidopsis Peptide Transporter Is a Member of a New Class of Membrane Transport Proteins

Abstract: An Arabidopsis peptide transport gene was cloned from an Arabidopsis cDNA library by functionally complementing a yeast peptide transport mutant. The Arabidopsis plant peptide transporter (AtPTR2) allowed growth of yeast cells on dipeptides and tripeptides but not peptides four residues and higher. The plant peptide transporter also conferred sensitivity to a number of ethionine-containing, toxic peptides of chain length three or less and restored the ability to take up radiolabeled dileucine at levels similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…However, the significant identity is predominantly found in the membrane-spanning domains, whereas the large extracellular loop, which contains 210 amino acid residues, shows only a 21% sequence match. Comparisons with nonmammalian POT family members like the nitrate transporter CHL1 from Arabidopsis thaliana (21) and the peptide permease PTR2 from Saccharomyces cerevisiae (22) reveal much lower sequence similarities.…”
Section: Resultsmentioning
confidence: 99%
“…However, the significant identity is predominantly found in the membrane-spanning domains, whereas the large extracellular loop, which contains 210 amino acid residues, shows only a 21% sequence match. Comparisons with nonmammalian POT family members like the nitrate transporter CHL1 from Arabidopsis thaliana (21) and the peptide permease PTR2 from Saccharomyces cerevisiae (22) reveal much lower sequence similarities.…”
Section: Resultsmentioning
confidence: 99%
“…The ϳ2.0-kb NotI cDNA fragment of AtPTR2 or fPTR2 was excised from plasmids pDTF1 (6) or pDTF4 (13), respectively, and cloned into pBluescript SKϩ (Stratagene, La Jolla, CA) to produce the restriction sites for the subsequent construction. For AtPTR2, the cDNA fragment containing 25 bp of the 5Ј untranslated region, 1758 bp of the coding region, and 141 bp of the 3Ј untranslated region were generated by digestion with EcoRI and XhaI (both in the multiple cloning site) and cloned into the EcoRI and XhaI sites of pGEMHE to give plasmid pGEMHE-AtPTR2.…”
Section: Methodsmentioning
confidence: 99%
“…In situ hybridization analysis showed that AtPTR2 is expressed in the embryo (12). The peptide transporter gene fPTR2 (originally named AtPTR2A) was also isolated by functional complementation of a yeast peptide transport mutant using an Arabidopsis cDNA library (13), but was later found not to be an Arabidopsis gene, but probably derived from a fungal contaminant (14).…”
mentioning
confidence: 99%
“…In 1994, five di/tripeptide transporter genes were identified independently in the rabbit (PepT1) [4], a fungus (fPTR2) [5,6], Arabidopsis (AtNTR1, renamed as AtPTR2) [7,8], yeast (PTR2) [9] and a bacterium (DtpT) [10] by functional cloning based on peptide transport activity when expressed in Xenopus oocytes (PepT1), complementation of a yeast mutant (fPTR2, AtPTR2 and yeast PTR2), or complementation of an Escherichia coli mutant (DtpT). These peptide transporters were found to share sequence similarity with the nitrate transporter CHL1, and, together, they form a new transporter family, called NRT1 (PTR).…”
Section: Nrt1(ptr) Familymentioning
confidence: 99%
“…Functional analysis of AtPTR2 and fungus fPTR2 (formerly AtPTR2-A, isolated by complementing a yeast mutant with an Arabidopsis cDNA library, but later found to be a gene from a fungal contaminant [5,6]) in Xenopus oocytes under voltage clamp conditions revealed that both transport a broad spectrum of dipeptides, with K m s ranging from 30 lM to 3 mM [14]. Similar to rabbit PepT1, AtPTR2 and fPTR2 prefer dipeptides; the tripeptide and amino acid transport activities being $60% and 10%, respectively, of the dipeptide activity [14].…”
Section: Dipeptide Transporters In the Nrt1(ptr) Familymentioning
confidence: 99%